2016
DOI: 10.1038/npjmgrav.2015.19
|View full text |Cite
|
Sign up to set email alerts
|

Circadian misalignment affects sleep and medication use before and during spaceflight

Abstract: Sleep deficiency and the use of sleep-promoting medication are prevalent during spaceflight. Operations frequently dictate work during the biological night and sleep during the biological day, which contribute to circadian misalignment. We investigated whether circadian misalignment was associated with adverse sleep outcomes before (preflight) and during spaceflight missions aboard the International Space Station (ISS). Actigraphy and photometry data for 21 astronauts were collected over 3,248 days of long-dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 41 publications
(31 reference statements)
2
93
3
Order By: Relevance
“…Our results are in accordance with previous NASA studies that demonstrate International Journal of Aerospace Engineering that even bones are affected over the course of long-term missions by loss of their total hip bone mass [14]. Moreover, our data add information to the list of known effects of space flights on the human body during long-duration missions such as muscle atrophy, bone demineralization, altered immune function [15,16], cardiovascular system dysfunction [17,18], and also alterations in sleep function [19]. A significant amount of data on the decrease in the performance of various groups of muscles has been collected from astronauts flying from 1989 to 1995 in NASA's orbiters or Russian capsules [20].…”
Section: Discussionsupporting
confidence: 78%
“…Our results are in accordance with previous NASA studies that demonstrate International Journal of Aerospace Engineering that even bones are affected over the course of long-term missions by loss of their total hip bone mass [14]. Moreover, our data add information to the list of known effects of space flights on the human body during long-duration missions such as muscle atrophy, bone demineralization, altered immune function [15,16], cardiovascular system dysfunction [17,18], and also alterations in sleep function [19]. A significant amount of data on the decrease in the performance of various groups of muscles has been collected from astronauts flying from 1989 to 1995 in NASA's orbiters or Russian capsules [20].…”
Section: Discussionsupporting
confidence: 78%
“…Aberrant regulation of telomere length has been associated with a number of human diseases and the link between physiological stress and aberrant regulation of telomere length is well documented . Stresses astronauts experience during spaceflight have been also shown to lead to alterations in telomere dynamics . For example, the NASA Twins Study found that the average telomere length in astronaut Scott Kelly's white blood cells increased over the course of his mission and returned to the pre‐flight length after his return to Earth .…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] Stresses astronauts experience during spaceflight have been also shown to lead to alterations in telomere dynamics. 5,[30][31][32][33] For example, the NASA Twins Study found that the average telomere length in astronaut Scott Kelly's white blood cells increased over the course of his mission and returned to the pre-flight length after his return to Earth. 5 It is hypothesized that changes in telomere length during spaceflight, such as those observed in Scott Kelly, may lead to tissue-specific molecular and cellular responses.…”
Section: Introductionmentioning
confidence: 99%
“…On Earth, humans have evolved a circadian rhythm based upon a 24 hour lightdark cycle and a gravitational force of 1 x g. Sleep quantity and quality are both negatively affected during spaceflight and the use of medication to promote sleep is prevalent, especially as astronauts are required to execute part of the mission where there is misalignment to the circadian rhythm, brought about by vehicle launch, orbit and docking times [6,[25][26][27]. Impairment of cognitive ability may be a concern and at worst constitute risk at the task or entire mission level with potentially life-threatening consequences.…”
Section: Sleepmentioning
confidence: 99%